2014
DOI: 10.3389/fpubh.2014.00141
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Coercive Interventions in Mental Health Care in Germany and the Netherlands. A Comparison of the Developments in Two Neighboring Countries

Abstract: In this review, we compare the use of coercion in mental health care in Germany and in the Netherlands. Legal frameworks and published data on involuntary commitment, involuntary medication, seclusion, and restraint are highlighted as well as the role of guidelines, training, and attitudes held by psychiatrists and the public. Legal procedures regulating involuntary admission and commitment are rather similar, and so is the percentage of involuntary admissions and the rate per 100,000 inhabitants. However, opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 43 publications
2
43
0
4
Order By: Relevance
“…; Steinert et al . ). While systematic reviews have failed to show convincing evidence for the efficacy of PRN medication use in the mental health setting (Chakrabarti et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Steinert et al . ). While systematic reviews have failed to show convincing evidence for the efficacy of PRN medication use in the mental health setting (Chakrabarti et al .…”
Section: Introductionmentioning
confidence: 97%
“…There are large differences in the use of seclusion or other coercive interventions across countries in Europe (Bak & Aggernaes, 2012;Janssen et al, 2009;Steinert, Noorthoorn, & Mulder, 2014). Serious safety hazards in psychiatric hospitals -such as aggression and violence of patients against staff, fellow patients or goods -are the main reason to use coercive interventions (Happell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, this report revealed that 10% of psychiatric patients in Jordan experienced coercive measures at least once during their admissions. In studies conducted in European countries, the reported levels of restraint and seclusion use was less than 1%. Therefore, the situation in Jordanian psychiatric settings indicates that the frequency of restraint and seclusion is critical and threatening and it may reflect the cultural beliefs and values within which a psychiatric system is situated …”
Section: Significance Of the Studymentioning
confidence: 93%
“…Previous studies have identified the concept of “least restrictive practices” to highlight the principle of trying multiple interventions before coercive measures are initiated. Such less restrictive alternatives are intended to de‐escalate, assess, and provide therapeutic interventions for patient safety and well‐being …”
Section: Literature Reviewmentioning
confidence: 99%